A Method for Finding the Routes of Mazes - Wu, Chang-Ming; Liaw, Der-Cherng; Lee, Hung-Tse (My University, 2018)
In this paper, we propose a potential modified route-searching algorithm to find all feasible paths in a new place which is like an unknown maze. The maze-like place is assumed to be a region constructed by grids and each grid is supposed to have at most four directions for moving. A searching algorithm is developed to accomplish the required tasks for patrolling every path in the new place. Based on the traditional depth-first graph traversal method, we build up a local-maze coordinate system to record the visited pathway. The main results of this paper will give an experiment simulation to demonstrate the success of proposed design.